Profitability as a Boundary Condition Between Global Trade Tensions, Capital Structure, and Firm Value: Evidence from Multinational Corporations in Indonesia - Udyono Udyono; Ariawan Ariawan; Indriani Mentaruk; Rajaman Rajaman; Muhammad Maula Razak (JURNAL ECONOMINA, 2026)
Increasing global trade uncertainty caused by changes in trade policies, geopolitical tensions, and international supply chain disruptions has created strategic challenges for multinational corporations highly exposed to the global economy. This study aims to analyze the effects of global trade tensions and capital structure on firm value and to examine the moderating role of profitability among multinational corporations operating in Indonesia. This research adopts a quantitative approach with an explanatory research design using data from multinational corporations listed on the Indonesia Stock Exchange during 2021–2024. The sample was selected through purposive sampling, resulting in 48 observations. Global trade tensions were measured using the World Trade Uncertainty Index (WTUI), capital structure was proxied by the Debt-to-Equity Ratio (DER), firm value was measured using Tobin’s Q, and profitability was represented by Return on Assets (ROA). Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA). The findings reveal that global trade tensions negatively and significantly affect firm value, while capital structure has a positive and significant effect. Profitability strengthens both relationships, indicating that firm value depends on internal capabilities and responses to global external pressures.